Challenges at the Frontiers of Science and Technology . - Aatre, V.K. (Defence Science Journal, 2010)
During the next 30 to 45 minutes I am going to share with you some of the information I have collected on the challenges and frontiers in science. Though I am going to cover several topics, most of them do not have much implication on technology .None seems to have relevance to DRDO and indeed some of them are not even topics of active research in India. Yet they are fascinating in themselves and I thought that it would riot be inappropriate to expose you to this fascinating world of challenges and frontiers' of science and technology-not much about technology but mostly Science.